Advancing chronic and acute wound healing with cold atmospheric plasma: cellular and molecular mechanisms, benefits, risks, and future directions - Raissi-Dehkordi, Nastaran; Raissi-Dehkordi, Negar; Ebrahimibagha, Hamed; Tayebi, Tahereh; Moeinabadi-Bidgoli, Kasra; Hassani, Mohammad; Niknejad, Hassan (Frontiers in Medicine, 2025)
Chronic and acute wounds represent significant challenges in healthcare, often leading to prolonged recovery times and increased complications. While chronic wounds, such as diabetic foot ulcers and venous leg ulcers, persist due to underlying conditions and biofilm formation, acute wounds, including surgical incisions and burns, can also benefit from innovative therapeutic approaches. Cold atmospheric plasma (CAP) has emerged as a promising non-invasive therapy capable of enhancing wound healing outcomes across both wound types. This review examines the cellular and molecular mechanisms by which CAP promotes wound repair, focusing on its modulation of inflammation, stimulation of angiogenesis, facilitation of tissue remodeling, and antimicrobial effects, which can potentially be used in regenerative medicine. CAP generates reactive oxygen and nitrogen species that influence key cellular processes, accelerating tissue regeneration while reducing bacterial load and preventing biofilm formation. Clinical applications of CAP have demonstrated its efficacy in improving wound healing metrics for both chronic and acute wounds. Despite promising results, translating CAP into routine clinical practice requires addressing challenges such as standardizing treatment protocols, assessing long-term safety, and developing portable devices. Future research should prioritize optimizing CAP parameters and exploring combination therapies to maximize its therapeutic potential. Overall, CAP represents a safe, effective, and versatile modality in wound management, with the potential to significantly improve patient outcomes in both chronic and acute wound care.